Perbandingan Konsep Adab Menurut Ibn Hajar Al-’Asqalany dengan Konsep Pendidikan Karakter di Indonesia - Nurdin, Indra Fajar; Indra Fajar Nurdin (Jurnal Pendidikan Islam, 2015)
Many crises that arise in our society recently, from an educational perspective, showed that the national education system has not performed optimally yet informing a society that has both skill-intellectuality and also spirituality, self-control, personality, and good morals. That multi-dimension crisis basically rooted in the decrease of nation moral quality e.g. the increase of corruption culture and conflict, the rise of criminality, and the decrease of work-ethos. A solution applied by the Indonesian government is by implementing character education, that has similar terms in Islamic education’s concept of Adab. The purpose of this research is to find out the concept of Adab by Ibn Hajar al-Asqalany and to find out the comparison and relevance between Ibn Hajar al-‘Asqalany’s concept of Adabwith the concept of character education in Indonesia. This research concludes that the concept of Adab based on Ibn Hajar al-‘Asqalany’s thought includes the fulfillment and development of adab to Allah Swt, adab to his/her self, and adab to another person. That concept of adab can be a basic step to determine the nine cores of character education that implemented in Indonesia.